Unmet need in Behcet's disease: most patients in routine follow-up continue to have oral ulcers - ALİBAZ ÖNER, FATMA; MUMCU, GONCA; DİRESKENELİ, RAFİ HANER; ERGUN, SAFİYE ATLAS TÜLİN (SPRINGER LONDON LTD, 2014)
The clinical course of Behcet's disease (BD) as a multisystemic disorder with a remitting-relapsing nature is insufficiently explored. As complete remission should be aimed in all inflammatory diseases, we investigated the frequency of complete remission in patients with BD followed in long-term, routine practice. In this retrospective study, 258 patients with BD who were regularly followed in outpatient clinics were assessed. The demographic and clinical data for active organ manifestations and treatment protocols were evaluated, and complete remission for this study was defined as no sign of any disease manifestation in the current visit and the preceding month. Two hundred fifty-eight patients with BD (F/M 130/128, mean age 41.1 +/- 11.5 years) were included to the study. Mucocutaneous disease was present in 48.4 % (n = 125). Mean visit number was 6.8 +/- 2.7, and mean follow-up duration was 45.8 +/- 36.5 months. Patients were clinically active in 67.2 % (n = 1,182) of the total visits (n = 1,757), which increased to 75.6 % (68.1-90.3) when the month preceding the visit was also included. The most common active manifestation was oral ulcers (39.4-63.2 %) followed by other mucocutaneous manifestations and musculoskeletal involvement. When multivariate analysis was performed, oral ulcers, which are the main cause of the clinical activity, negatively correlated with immunosuppressive treatments (beta = -0.356, p < 0.000) and age (beta = -0.183, p = 0.04). It is fairly difficult to achieve complete remission in BD with current therapeutic regimens. The reluctance of the clinician to be aggressive for some BD manifestations with low morbidity, such as mucocutaneous lesions and arthritis, might be influencing the continuous, low-disease activity state, especially due to oral ulcers, in BD patients.
Keywords: Behcet's disease; Complete remission; Oral ulcer; RECURRENT APHTHOUS STOMATITIS; TREAT-TO-TARGET; QUALITY-OF-LIFE; INFLIXIMAB; MANIFESTATIONS